SOCIETIES IN TRANSFORMATION - SOARES, K. C. (Revista Brasileira de Administração Política, 2016)
The world as a community is growing closer together every day with transformations in our social organizations and societies occurring at accelerated rates. Thus, the social changes presently in process are stimulating in the integration of actions and results; integrations of human groupings; and socio-economic, cultural, political, technological integrations at fast paces unheard of in our recent history. These changes and transformations are a dynamic reality which, bringing peoples and countries closer together, also represent many challenges. The following reflections are written with the intent of sharing thoughts and experiences, and provoking exchanges. By learning from each other we are better able to utilize appropriate actions and realize achievements that are meaningful for the social organizations in which we interact. Thus, by helping each other avoid pitfalls already experienced, and by building upon shared experiences, we can effectively contribute to the dynamic changes now sweeping through our world community.